Hiring a Homosexual, Taking a Risk? A Lab Experiment on Employment Discrimination and Risk Aversion - Stijn Baert (Institute for the Study of Labor (IZA), 2015)
We investigate risk aversion as a driver of labour market discrimination against homosexual men. We show that more hiring discrimination by more risk-averse employers is consistent with taste-based and statistical discrimination. To test this hypothesis we conduct a scenario experiment in which experimental employers make a hiring decision concerning a heterosexual or homosexual job candidate. In addition, participants are surveyed on their risk aversion and other characteristics that might correlate with this risk aversion. Analysis of the (post-)experimental data confirms our hypothesis. The probability of a beneficial hiring decision for homosexual candidates decreases by 31.7% when employers are a standard deviation more risk-averse.
Keywords: C91; J15; J71; 330; hiring discrimination; statistical discrimination; sexual orientation; scenario experiment; risk aversion